Copper and Zinc Homeostasis: Lessons from Drosophila melanogaster - Navarro, Juan A.; Schneuwly, Stephan (Frontiers in Genetics, 2017)
Maintenance of metal homeostasis is crucial for many different enzymatic activities and in turn for cell function and survival. In addition, cells display detoxification and protective mechanisms against toxic accumulation of metals. Perturbation of any of these processes normally leads to cellular dysfunction and finally to cell death. In the last years, loss of metal regulation has been described as a common pathological feature in many human neurodegenerative diseases. However, in most cases, it is still a matter of debate whether such dyshomeostasis is a primary or a secondary downstream defect. In this review, we will summarize and critically evaluate the contribution of Drosophila to model human diseases that involve altered metabolism of metals or in which metal dyshomeostasis influence their pathobiology. As a prerequisite to use Drosophila as a model, we will recapitulate and describe the main features of core genes involved in copper and zinc metabolism that are conserved between mammals and flies. Drosophila presents some unique strengths to be at the forefront of neurobiological studies. The number of genetic tools, the possibility to easily test genetic interactions in vivo and the feasibility to perform unbiased genetic and pharmacological screens are some of the most prominent advantages of the fruitfly. In this work, we will pay special attention to the most important results reported in fly models to unveil the role of copper and zinc in cellular degeneration and their influence in the development and progression of human neurodegenerative pathologies such as Parkinson's disease, Alzheimer's disease, Huntington's disease, Friedreich's Ataxia or Menkes, and Wilson's diseases. Finally, we show how these studies performed in the fly have allowed to give further insight into the influence of copper and zinc in the molecular and cellular causes and consequences underlying these diseases as well as the discovery of new therapeutic strategies, which had not yet been described in other model systems.